TELEMEDICINE: HEALTHCARE FACILITIES READINESS TO CHANGE - Dewi, Arlina (Universitas Muhammadiyah Tapanuli Selatan, 2023)
Background: In the era of the covid-19 pandemic, health facilities have challenges in optimizing health services, especially continuity of care. The results of the patient visit survey decreased by 50%. Health facilities must be able to make changes to access to care to be more flexible and effective. Objective: This community service aims to identify the readiness of health facilities for changes in health services with telemedicine. Method: This community service method uses an action research method which is divided into three stages, including the first stage identifying readiness for changes in health services with telemedicine; the second stage is conducting training on the implementation of telemedicine; the third stage evaluates the application of telemedicine-based on the number of patients who use it three months (January-March 2022) after the training. This service instrument uses a google form with 35 statement items given to the four primary clinics (10 respondents)—quantitative data analysis with frequency distribution. Findings: The results of this community service indicate that the readiness of health facilities to implement telemedicine reaches a score of 3.08 (ready) with four supporting factors including staff situation (2.74), change target attributes (2.80), management support (2.99), and attributes change (3.02). The readiness of health facilities to implement telemedicine after training has a positive impact on increasing the number of telemedicine patients by 260%. Conclusion: Changes in health service methods require complex readiness both from the management side as supporting facilities and increasing staff skills and the ability and willingness of staff as health service providers.